PROPHYLAXIS OF PNEUMOCOCCAL INFECTION WITH VACCINES FOR PREVENTION OF COMPLICATIONS AND DEATH IN PATIENTS WITH INFLUENZA - M.P. Kostinov; D.V. Pakhomov; O.O. Magarshak ("Paediatrician" Publishers LLC, 2010)
The article analyzes the role of pneumococcal infection as a cause of complications and death in patients with influenza. Authors performed historic analysis of data on development of bacterial complications in period of influenza pandemic. Possible pathogenetic mechanisms of bacterial co-infection development are characterizeed. Effective vaccination of children with pneumococcal conjugated vaccine is able to decrease morbidity and mortality in common population and in group of high risk patients.Key words: children, pneumococcal infection, influenza, complications, mortality, vaccination.(Voprosy sovremennoi pediatrii - Current Pediatrics. 2010;9(6):131-134)